Sistem Produksi dan Potensi Ekonomi Peternakan Kambing Lokal Bligon di Desa Girimulo, Kecamatan Panggang, Gunungkidul - Widiati, Rini; Kusumastuti, Tri Anggraeni (Universitas Sebelas Maret (UNS), 2017)
This study was aimed to determine the economic potential and factors that influenced to the income of the Bligon local goat farming in Girimulyo Village, Panggang sub District of Gunungkidul. Data was collected from 30 Bligon goat farmers in the study area which taken purposively as the respondents. Data were collected by direct in-depth interviews to the respondents using questionnaires. Both quantitative and qualitative data were analysed. Enterprise Budgeting was made to analyze the economic potential of Bligon goat farming in the form of net farm income and return to labor and management on the production system that farmers doing. Furthermore, to determine the factors that influence the income of farmers using multiple regression analysis. The results showed that the Bligon goat farming with average maintenance of 2 heads of productive females and 1 head fattening male can give net farm income of Rp 936.463, - or in the form of return to labor and management amounting to Rp 2.380.241,-/ farmer/ year. Factors that significantly positive have affect to the farmer income were number of goat ownership (P<0,05) and litter size (P<0,01), while mortality have negative effect (P<0,5). The Bligon goat farming was a potential alternative that can developed to generate income for rural communities. However, it is a challenge for scientists to develop technologies that support the improvement of production aspects associated with kidding interval, litter size and mortality.